2023
DOI: 10.21037/qims-22-836
|View full text |Cite
|
Sign up to set email alerts
|

Using radiomics based on multicenter magnetic resonance images to predict isocitrate dehydrogenase mutation status of gliomas

Abstract: Background: Isocitrate dehydrogenase (IDH) mutation status is an important biomarker for the treatment strategy selection and prognosis evaluation of glioma. The purpose of this study is to predict the IDH mutation status of gliomas based on multicenter magnetic resonance (MR) images using radiomic models, which were composed from the selected radiomics features and logistic regression (LR), support vector machine (SVM), and LR least absolute shrinkage and selection operator (LASSO) classifiers. Methods:We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Xu et al (25) reported no notable disparity in early recurrence after curative resection between patients with M0 HCC and patients with M1 HCC; however, the M2 grade was potentially associated with a poorer prognosis in patients with HCC. Although numerous studies (6,7,19,21,22,(26)(27)(28) have focused on predicting MVI status in patients with HCC, few have explored the preoperative grading of M2. To the best of our knowledge, no previous attempts have been made to use clinical and MRI features for preoperative prediction of the M2 classification in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (25) reported no notable disparity in early recurrence after curative resection between patients with M0 HCC and patients with M1 HCC; however, the M2 grade was potentially associated with a poorer prognosis in patients with HCC. Although numerous studies (6,7,19,21,22,(26)(27)(28) have focused on predicting MVI status in patients with HCC, few have explored the preoperative grading of M2. To the best of our knowledge, no previous attempts have been made to use clinical and MRI features for preoperative prediction of the M2 classification in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The analyzed images were mainly institution-based (imaged locally or in a multicentric setting), with only ten studies using a public cohort for external validation [7,11,[19][20][21][22][23][24][25][26] and four studies using public datasets (such as the BraTs 2021 [27][28][29][30]) without including local data. The studies utilizing public datasets could include significantly more patients than those with local imaging data.…”
Section: Data Sourcesmentioning
confidence: 99%
“…This includes remarkable remission rates, durable local control, and extended survival times, whether applied alone or in combination with systemic treatments. [8][9][10][11][12][13] Specifically, unresectable HCC patients with MVI, possessing good liver function and well-developed periportal collateral circulation, may achieve substantial clinical benefits from TACE or combined TACE plus RT treatment. Moreover, the administration of sorafenib in conjunction with TACE and/or RT has demonstrated encouraging clinical outcomes for patients with locally advanced HCC.…”
Section: Introductionmentioning
confidence: 99%